2017
DOI: 10.3389/fgene.2017.00040
|View full text |Cite
|
Sign up to set email alerts
|

Disease Resistance and the Definition of Genetic Enhancement

Abstract: Recent gene editing experiments carried out in human embryos have raised the question of whether interventions like the introduction of a CCR5-Δ32 deletion, which could provide heritable resistance to HIV infection, ought to be considered enhancements. Many authors have used the term “enhancement” in different ways, some based on patients’ biomedical outcomes and others on their social context. These classifications are often considered overly imprecise. Nevertheless, the concept of “enhancement” could affect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 43 publications
0
14
0
1
Order By: Relevance
“…Though current translational projects are mostly focused on prevention of monogenic disorders, there are other potential applications of GGE that have received some attention. The most prominent is the use of GGE to lower risk of communicable or non-communicable disease, such as editing to confer limited or full immunity to common pathogens or to lower risk of chronic conditions such as heart disease [66][67][68]. The experiments conducted by He Jiankui were of this type-as discussed in the "Introduction" section, He was attempting to disable the CCR5 gene and so confer some immunity to HIV infection.…”
Section: What Is the Potential Clinical Utility Of Germline Gene Editmentioning
confidence: 99%
“…Though current translational projects are mostly focused on prevention of monogenic disorders, there are other potential applications of GGE that have received some attention. The most prominent is the use of GGE to lower risk of communicable or non-communicable disease, such as editing to confer limited or full immunity to common pathogens or to lower risk of chronic conditions such as heart disease [66][67][68]. The experiments conducted by He Jiankui were of this type-as discussed in the "Introduction" section, He was attempting to disable the CCR5 gene and so confer some immunity to HIV infection.…”
Section: What Is the Potential Clinical Utility Of Germline Gene Editmentioning
confidence: 99%
“…How people evaluate risks can also be influenced by a hazard's 'personality' profile. Decades of psychometric research has identified key hazard characteristics important in shaping perceived risk (Slovic 1987;Sparks and Shepherd 1994;Finucane and Holup 2005). In particular, two main dimensions can drive risk perceptions: the extent to which a hazard is (1) unknown and (2) dreaded.…”
Section: Risk Perceptions Of Human Gene Editingmentioning
confidence: 99%
“…We engage this same values discourse when we consider whether to eradicate diseases such as polio or measles. In the Western world, we have had the privilege of deciding that some diseases have no redeeming value and are worth eradicating because they can do incredible damage to the human race (So et al 2017;Juengst et al 2018). Many rare disease patients may argue that their diseases are more than mere differences, that they are solely harmful in nature, and that they have no redeeming value.…”
Section: Advocacymentioning
confidence: 99%